Community optimized management for better eating after hospital sTay among geriatric patients of poor socio-economic status - The COMEAT study. Issue 8 (August 2022) - Theilla, Miriam; Singer, Pierre; Tadmor, Boaz; Bendavid, Itai; Hellerman, Moran; Kagan, Ilya
Summary: Introduction: In patients suffering from disease-related and socioeconomic malnutrition and being discharged from hospital, continuity of care is challenging. Lack of adequate nutrition may lead to increase in morbidity and mortality. The aim of this study was to overcome the handicap of limited nutrition access in this category of patients and to study its consequences on clinical outcome. Methods: Hospitalized patients screened to be at risk of malnutrition were approached and if diagnosed as suffering from malnutrition and from limited financial resources, they were randomized to receive a delivered daily dinner tray for 6 months and an assistance during the meal by a philanthropic association, or to regular food. At entry to the study, patients were assessed by indirect calorimetry, bioimpedance, Hospital Anxiety and Depression Scale (HADS), Functional independence measure (FIM) and SF 36 quality of life questionnaire. The latest questionnaires were reproduced after 3 and 6 months. Survival was followed at 6 months. The student t-test, the paired t-test, ANOVA were used. 180 days survival curves were expressed using the Kaplan-Meier method. Results: 631 patients were screened and 60 patients were randomized. There was no difference between groups. Survival at 6 months was improved significantly in the intervention group (87%) compared to the control group (65%, p<005). HADS did significantly improve at 3 months and other parameters (FIM, SF 36) were not changed significantly. Conclusions: In hospitalized patients at nutritional risk, lunch home delivery, supported by a physical company after hospital discharge was associated with significantly lower mortality rates and improved depression and anxiety scores in elderly patients suffering from socioeconomic related malnutrition